Factor completely: 15x3y2 25x2y2 5xy2

Question

Asked 5/11/2012 7:42:07 PM

Updated 3/19/2014 11:03:13 PM

9 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [3/19/2014 10:50:23 PM]

s

darkangel20|Points 335|

darkangel20|Points 335|

strikeapose|Points 40|

SecretAgent|Points 1768|

jher000|Points 7242|

yestfl|Points 1444|

thederby|Points 1164|

JuliaMunz|Points 55|

Question

Asked 5/11/2012 7:42:07 PM

Updated 3/19/2014 11:03:13 PM

9 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [3/19/2014 10:50:23 PM]

Rating

3

x^2 + 8x+ 12 = (x + 2)(x + 6)

Added 3/19/2014 10:50:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:28 PM]

3

16x^2 - 49 = (4x + 7)(4x - 7)

Added 3/19/2014 10:51:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:29 PM]

3

(4x^2+6x+3)+(2x^2-5x-3)

= 4x^2+6x+3+2x^2-5x-3

= 6x^2+x

= 4x^2+6x+3+2x^2-5x-3

= 6x^2+x

Added 3/19/2014 10:52:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:29 PM]

3

(5x^3 + 15x - 10x) / 5x

= 5x(x^2 + 3 - 2)/5x

= x^2 + 3 - 2

= x^2 + 1

= 5x(x^2 + 3 - 2)/5x

= x^2 + 3 - 2

= x^2 + 1

Added 3/19/2014 10:54:23 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:30 PM]

3

3x - { 4y - 2[ 3y - ( 2 - 2y)]}

= 3x - [4y - 2(3y - 2 + 2y)]

= 3x - [4y - 2(5y - 2)]

= 3x - (4y -10y + 4)

= 3x - (-6y + 4)

= 3x + 6y - 4

= 3x - [4y - 2(3y - 2 + 2y)]

= 3x - [4y - 2(5y - 2)]

= 3x - (4y -10y + 4)

= 3x - (-6y + 4)

= 3x + 6y - 4

Added 3/19/2014 10:57:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:32 PM]

3

The area of a square is 25 sq meters. Its side is sqrt 25 = 5 meters, so the perimeter of the square = 5*4 = 20 meters.

Added 3/19/2014 10:59:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:33 PM]

3

when x= -3,

x^2 + 9x +7

= (-3)^2 + 9(-3) + 7

= 9 - 27 + 7

= - 18 + 7

= - 11

x^2 + 9x +7

= (-3)^2 + 9(-3) + 7

= 9 - 27 + 7

= - 18 + 7

= - 11

Added 3/19/2014 11:01:04 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:34 PM]

3

-4x + 7 = 35

-4x = 35 - 7 = 28

x = 28/-4 = - 7

-4x = 35 - 7 = 28

x = 28/-4 = - 7

Added 3/19/2014 11:02:11 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:35 PM]

3

-2(x - 4) = -3(x + 8)

-2x + 8 = -3x - 24

-2x + 3x = -24 - 8

x = - 32

-2x + 8 = -3x - 24

-2x + 3x = -24 - 8

x = - 32

Added 3/19/2014 11:03:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/19/2014 11:15:36 PM]

Simplify 6(y + 7) User: 5x + 7 + 9x - 4 User: multiply (5xy^4)(2x^2y) **Weegy:** Do you have more to the equation? (More)

Question

Not Answered

Updated 6/16/2014 2:09:43 PM

2 Answers/Comments

5x + 7 + 9x - 4 = 14x + 3

Added 6/16/2014 2:09:26 PM

This answer has been confirmed as correct and helpful.

(5xy^4)(2x^2y) = 10x^3y^5

Added 6/16/2014 2:09:43 PM

This answer has been confirmed as correct and helpful.

31,420,812

questions answered

denyang

$415.35

Hearts 9,375 Views 3,027,380 Streams 923

sampi1890

$315.05

Hearts 6,565 Views 3,081,044 Streams 871

Flora1988

$305.85

Hearts 6,764 Views 2,016,931 Streams 669

maydj

$292.25

Hearts 6,480 Views 2,379,417 Streams 714

PeachyStream97

$286.00

Hearts 6,366 Views 885,156 Streams 287

miyaka

$282.80

Hearts 6,502 Views 2,661,637 Streams 851

phpmicro

$244.70

Hearts 5,035 Views 1,750,557 Streams 501

jpmind

$209.60

Hearts 4,733 Views 553,571 Streams 175

There are no comments.